Local Campaign Effect On Tourism Supply Chain During The Times Of Covid-19 - Sthandiwe Mkhize; Portia Pearl Siyanda Sifolo (Journal on Tourism & Sustainability, 2022)
Leveraging of tourism's potential during the challenging times (such as Covid-19 pandemic) through the initiatives such as the “buy local campaign” has a critical effect in the tourism supply chain and contribute towards service excellence, creating and sustaining quality jobs. Hence, stakeholders within the supply chain are encouraged to coordinate and collaborate through different channels. This paper explores effect of a “Buy local campaign” on businesses operating in the tourism supply chain. Web Content Analysis was adopted to identify common themes likely to impact the ‘buy local campaign’ during and post covid-19 in the South African context. Although the covid-19 pandemic presented challenges in several value chains, there exist “new ways of conducting a local campaign for collective benefits”. Campaigns encourages the nation to contribute towards the economic growth and prosperity of the country through buying locally produced goods and services.